Rounding of birth weights in a neonatal intensive care unit over 20 years: an analysis of a large cohort study. Issue 12 (5th December 2013) - Emmerson, Anthony J; Roberts, Stephen A
Abstract : Objective: To determine the frequency of birth weight digit preference for infants admitted to a large neonatal intensive care unit (NICU), the scale of rounding and its dependence on birth weight, and time and the impact on prescribing accuracy. Design: A consecutive cohort of birth weights extracted retrospectively from a single clinical database. Setting and participants: Birth weights from 9170 inborn infants recorded on an electronic prescribing database admitted to NICU over 20 years. Statistical approach: Data are presented for the frequency of each of the possible pairs of final digits. A statistical model of digit preference assuming rounding is used to quantify the proportions rounding to specific accuracy levels. These proportions are compared between those <1000 g and those above and over the 20-year time period. Results: From a population of 9170 infants admitted over 20 years, there was a highly statistically significant digit bias with an increased prevalence of multiples of 100 (p<0.0001), 50 (p=0.007), 20 (p<0.0001), 10 (p<0.0001), 5 (p<0.0001) and 2 (p=0.0005). There was clear evidence of a reduced 100 g digit bias for infants 500 and 1000 g (0%) compared with those between 1000 and 4500 g (3.7%). The maximum birth weight error due to digit bias for all infants was 5%. There was clear evidence of an improvement in accuracy over 20 years. Conclusions: Digit bias in birth weights over 20 years in a tertiary NICU is highly significant at the 100, 50, 20, 10, 5 and 2-digit levels. There has been a substantial improvement in the accuracy of birth weight measurements over 20 years. The likely maximum error due to birth weight digit bias is 5% and is within an acceptable tolerance for drug dosing even at very low birth weights.